The first discovery of Tc1 transposons in yeast - Chang, Jia; Duan, Guangyou; Li, Wenjing; Yau, Tung On; Liu, Chang; Cui, Jianlin; Xue, Huaijun; Bu, Wenjun; Hu, Yanping; Gao, Shan (Frontiers in Microbiology, 2023)
Background: Identification of transposons without close homologs is still a difficult task. IS630/Tc1/mariner transposons, classified into a superfamily, are probably the most widespread DNA transposons in nature. Tc1/mariner transposons have been discovered in animals, plants, and filamentous fungi, however, not in yeast. Results: In the present study, we report the discovery of two intact Tc1 transposons in yeast and filamentous fungi, respectively. The first one, named Tc1-OP1 (DD40E), represents Tc1 transposons in Ogataea parapolymorpha. The second one, named Tc1-MP1 (DD34E), represents Tc1 transposons in the Rhizopodaceae and Mucoraceae families. Tc1-OP1 and Tc1-MP1 have homologs in bacteria, but no homologs in plants and animals. As a homolog of Tc1-OP1 and Tc1-MP1, IS630-AB1 (DD34E) was discovered as an IS630 transposon in Acinetobacter spp. Conclusions: Tc1-OP1 is not only the first reported Tc1 transposon in yeast, but also the first reported nonclassical Tc1 transposon. Tc1-OP1 is the largest of IS630/Tc1/mariner transposons reported to date and significantly different from others. Notably, Tc1-OP1 encodes a serine-rich protein and a transposase, challenging the classical model of Tc1 transposons. The phylogenetic relationships of Tc1-OP1, Tc1-MP1 and IS630-AB1 indicated that these transposons had evolved from a common ancestor. Tc1-OP1, Tc1-MP1 and IS630-AB1 can be used as reference sequences to facilitate the identification of IS630/Tc1/mariner transposons. More Tc1/mariner transposons will be identified in yeast, following our discovery.